The function for y in terms of x is:
f(x) = 4x + 11
The function for x in terms of y is:
g(y) = (y - 11)/4.
we start with the relation:
y = 4x + 11
And we want a rule:
y = f(x)
Then is trivial to see that:
f(x) = 4x + 11.
That is the rule for the function.
Now we want to fund a function g, that defines x on terms of y, so we need to write:
x = g(y).
To do that, we can isolate x on the given relation:
y = 4x + 11
y - 11 = 4x
(y - 11)/4 = x
Then we have:
x = g(y) = (y - 11)/4
If you want to learn more about functions:
https://brainly.com/question/4025726
#SPJ1